2014
DOI: 10.1097/qai.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report

Abstract: Elite controllers (ECs) maintain undetectable HIV viral loads without antiretroviral therapy (ART), but are at increased risk of serious non-AIDS conditions (SNA). We assessed the impact of ART in ECs on gut immune dysfunction and biomarkers predicting SNA (blood CD4/CD8 ratio, plasma IL-6, D-dimer levels). At baseline, ECs had elevated IL-6 and D-dimer levels and reduced CD4/CD8 ratio compared to HIV-uninfected controls, but no difference in microbial translocation or gut CD4 subsets. ART increased CD4/CD8 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Vesterbacka et al (2017) found that EC’s have a richer gut microbiota with a distinct metabolic profile that resembles that of HIV-uninfected adults, and that is vastly unique from ART-treated HIV-infected individuals (Table 1) [43**]. The increased frequency of Th17 cells in the gut mucosa of EC’s compared to ART-treated HIV-infected adults [48] may be responsible for their low levels of inflammation and seemingly “normal” gut microbiome. Understanding whether there is a direct interaction between the microbiome and reduced inflammation and immune activation and smaller reservoirs in ECs could inform pathogenesis and treatment of dysbiosis in HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Vesterbacka et al (2017) found that EC’s have a richer gut microbiota with a distinct metabolic profile that resembles that of HIV-uninfected adults, and that is vastly unique from ART-treated HIV-infected individuals (Table 1) [43**]. The increased frequency of Th17 cells in the gut mucosa of EC’s compared to ART-treated HIV-infected adults [48] may be responsible for their low levels of inflammation and seemingly “normal” gut microbiome. Understanding whether there is a direct interaction between the microbiome and reduced inflammation and immune activation and smaller reservoirs in ECs could inform pathogenesis and treatment of dysbiosis in HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with these findings, also high levels of similar markers prior to the initiation of antiretrovirals were shown to predict non-AIDS morbid events on stable treatment [ 11 ] (Table 1 ). In contrast however, administration of cART in elite controllers did not affect markers of microbial translocation and inflammation [ 12 ]. In a recent report, our group showed that pre-cART levels of CRP, but not sCD14, LPS or EndoCAb predicted clinical events in a large cohort of treated HIV-infected subjects [ 13 ] and suggest, together with other literature evidence, that the occurrence of non-AIDS conditions may be only in part related to gut damage and microbial translocation (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, HIV-1 encodes for various TLR7/8 ligands that can mediate direct activation of the immune system in vitro (2224). Likewise, HIV-driven gut barrier damage is not reverted by cART (2528) and leads to the passage of microbial products in peripheral blood, mainly lipopolysaccharide (LPS), which is a TLR4 agonist (29, 30). Circulating LPS levels have been associated with immune activation both in treated and untreated HIV (3135); furthermore, exogenous in vivo LPS administration has been described to enhance immune activation (34).…”
Section: Introductionmentioning
confidence: 99%